Rethinking the link between consultation and conflict: Lessons from Bolivia's gas sector - Schilling-Vacaflor, Almut (Canadian Journal of Development Studies-Revue Canadienne D Etudes Du Developpement, 2014)
This article sheds light on 26 consultations in Bolivia's gas sector (2007-2012) and challenges simplified conceptions of prior consultation as a tool for conflict prevention and resolution. It shows that consultations do not only appease, but also exacerbate conflicts, as they are used for negotiating broader grievances. The study further argues that, in the short term, narrow consultations repress conflicts by limiting opportunities to mobilise against extractive projects. It also reveals that the degree of conflict and prevention potential of consultations varies according to the affected groups and highlights the ambiguous effects of the entanglement of consultations and compensations.
CRIS-Team Scopus Importer:2023-11-20
Keywords: Bolivia; extractive industry; indigenous peoples; prior consultation; socio-environmental conflicts